A novel synthetic approach to Pyrazolooxazines. One‐pot synthesis of Pyrazolo[5, 1‐c][1, 4]oxazine derivatives from 2, 2‐dichlorovinylacetophenones. (6th November 2022) - Guirado, Antonio; Martiz, Bruno; Vera, María; Andreu, Raquel; Bautista, Delia
Abstract: New convenient synthetic methods in pyrazoline and pyrazolooxazine chemistry have been developed starting from 2, 2‐dichlorovinylacetophenones 4, whose reaction with 2‐hydroxyethylhydrazine directly gave hitherto unknown 3‐aryl‐5‐dichloromethyl‐1‐(2‐hydroxiethyl)‐2‐pyrazolines 7 in high yields. These were found to be able to undergo cyclization to afford 2‐aryl‐6, 7‐dihydro‐4 H ‐pyrazolo[5, 1‐ c ][1, 4]oxazines 10 upon treatment with sodium hydride. Compounds 10 could also easily be obtained in near quantitative yields by a one‐pot preparative process involving reaction of compounds 4 with 2‐hydroxyethylhydrazine followed by addition of sodium hydroxide. The simplicity and the high yield of this reaction make it much more attractive than the previously described multistep procedure. The molecular structure of 2‐(4‐chlorophenyl)‐6, 7‐dihydro‐4 H ‐pyrazolo[5, 1‐ c ][1, 4]oxazine 10c was determined by x‐ray crystallography. Abstract : New convenient methods to access to 2‐aryl‐6, 7‐dihydro‐4 H ‐pyrazolo[5, 1‐c][1, 4]oxazines and 3‐aryl‐5‐dichloromethyl‐1‐(2‐hydroxiethyl)‐2‐pyrazolines